Developing modernization indicators for the People Republic of China key considerations and a proposed framework. (East Asia working papers., 2020)
The PRC is in a modernization process that it expects to achieve by 2035. This requires a national indicator to gauge the progress and level of the country modernization drive. In this paper, the modernization indicator applied is structured on thematic categories, subcategories, and intersection. It examines four major policy implications for the PRC that can be more durable and successful if coupled with effective division of labor and synergy with stakeholders.